“For whoever has will be given more”? Land rental decisions and technical efficiency in Ukraine - Vasyl Kvartiuk; Eduard Bukin; Thomas Herzfeld (Land Use Policy, 2024)
Land rental markets had played a critical role in providing farms access to Ukraine's agricultural land before the ban on land sales was lifted in 2021. This paper examines whether rental-based land relations can promote land use by more productive farms in the context of imperfect institutions. In particular, we examine whether Ukrainian farms' decisions to rent land are linked to their agricultural ability. Utilizing a rich panel of more than 16,000 Ukrainian commercial agricultural producers for 2005–2015, we analyze demand-side determinants of participation in the land rental market. The evidence suggests that farms' total factor productivity is disconnected from their decisions to rent land. Land accumulation appears to be driven by other context-related factors, including existing local land concentration and orientation toward cash crop production. Results call for launching a land sales market and improving rental market infrastructure because these measures can align land rental prices with the value of the marginal product of land.
Keywords: 630; land rental market; efficiency; land concentration; land reform